Dihydrochalcones and flavonolignans from Iryanthera lancifolia - Silva, DHS; Davino, S. C.; Barros, SBD; Yoshida, M. (Amer Chemical Soc, 1999)
An extract from the pericarps of I. lancifolia afforded two dihydrochalcones (1 and 2) and two flavonolignans (3 and 4), with compounds 2-4 being of novel structure. The antioxidant activities of compounds 1-4 were evaluated through the measurement of malondialdehyde production, and Q(1/2) (concentration necessary far 50% inhibition of autoxidation) data were calculated. The Q(1/2) values obtained for 1-4 and the standard compounds a-tocopherol and quercetin were 6.9, 4.7, 5.5, 4.8, 12.1, and 7.6 mu g/mL, respectively.